The Effectiveness of Writing Journal and Feedback on Increasing Writing Proficiency at University Students - Ninik Farikha (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2020)
The practice of giving feedback in teaching and learning process seems to be unclear.Unclear is an inconsistent feedback given by the teacher during teaching learning process. Teacherrarely gave the evaluation because giving feedback will be time-consuming. Teacher used students‟task sheet instantly. Teachers need to check the students‟ work and give the feedback to students‟task. This way makes students aware that something “wrong” appears and they need to consider itto their improvement. This study intends to investigate the difference between students‟achievement in writing proficiency who are taught by using writing journal technique and givenfeedback and those who are not. The research design used in this research was quasi experimentaldesign. Experimental design is the conceptual outline in doing experiment. In this experimentaldesign, the researcher used two English Program classes of IAIN Kediri. First class wasexperimental class which is treated using writing journal and giving feedback while the second classwas control class which is not treated using writing journal and giving feedback. The resultsrevealed that using writing journal technique in learning was effective to increase the students‟writing ability. It was good technique to improve students‟ ability in writing proficiency.